A conceptual framework of Maqasidic human wellbeing index - Ahmad Sarkawi, Azila; Abdullah, Muhammad Faris; Abdullah, Alias; Khazani, Nur Amilin (2017)
Amongst the 57 members of the Organisation of the Islamic Conference (OIC) countries, Malaysia was rated as number one in the Islamicity Index, Islamic Index of Wellbeing and Global Muslim Travel Index studies. In Malaysia, the Institute of Islamic Understanding Malaysia (IKIM), Department of Islamic Development Malaysia (JAKIM), and the Institute of Community and Peace Studies (PEKKA) have also published their own Islamic-oriented wellbeing indexes. However, these Indexes lack the integration of Maqasid al-Shari’ah (the objectives of Islamic laws) concept, which is based on the preservation of five essentials namely faith, self, intellect, posterity and property. Hence, to address this gap, this study proposes a conceptual framework of human wellbeing index in the context of Maqasid al-Shari’ah. This study is exploratory in nature employing rigorous library research and content analysis technique. The three basic principles of Iman (faith), Islam (submission) and Ihsan (benevolence) are discussed in relation to the five essentials of Maqasid al-Shari’ah. Their application at the three levels of the social structure i.e. individual, family and community is elaborated to establish a maqasidic approach for human wellbeing. This approach is then linked to the five established themes of human wellbeing domains notably politics and governance, economy, social and culture, environment, and infrastructure. Finally, a conceptual framework of human wellbeing index is proposed to provide the maqasidic foundation for the measurement of human wellbeing.